An interethnic companion to Asian American literature - Cheung, King-Kok (Cambridge University Press, 1997)
This book is a survey of literature by North American writers of Asian descent, in terms of both national origins (Chinese, Filipino, Japanese, Korean, South Asian, Vietnamese) and shared concerns. It introduces readers to the distinctive literary history of each group of writers and discusses issues that connect or divide these different groups. Part One provides a literary history of each constituent national group and underlines salient historical events that have affected its writing.